A study of new particle formation in the marine boundary layer over the central Arctic Ocean using a flexible multicomponent aerosol dynamic model - Karl, Matthias; Leck, Caroline; Gross, Allan; Pirjola, Liisa (Tellus B: Chemical and Physical Meteorology, 2016)
Peer reviewed